Intended Versus Enacted Curriculum and Practice in Secondary Schools’ Science Classrooms: Evidence from Selected Districts of Nepal - Tripathi, Yashodham; Aryal, Arjun; Panthee, Chintamani; Yadav, Mukesh Kumar; Pande, Shiv Ram (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: Nepal’s secondary science curriculum emphasises learner-centred, inquiry-oriented pedagogy, yet classroom practice is widely perceived as textbook-bound. This study examined the alignment between intended and enacted curricula and practice in secondary science classrooms. Methods: We used a mixed-methods, descriptive–exploratory design. Disproportionate stratified random sampling and pragmatic snowballing identified secondary science teachers across selected localities in both districts. Data sources included a structured questionnaire, classroom and meeting observations, semi-structured interviews, focus group discussions (FGDs), key informant interviews (KIIs), and case studies; tools were pre-tested and refined before full administration. The final sample comprised 149 teachers. Results: Classroom practice was predominantly transmission-oriented. Most teachers read from the textbook during instruction (77.18%; 115/149), indicating strong reliance on text over concept-driven teaching. Lesson planning was rarely child-centred: no teachers reported fully child-centred plans, and the modal category was “least child-centred” (39.59%). Lecture-dominated methodological choices (39.59%), whereas heuristic/inquiry approaches were uncommon (4.02%). Practical work was infrequent: over two-thirds reported never using a practical approach (71.14%). Science-popularising activities were scarce, with reports from only a small minority of schools. Training profiles diverged by sector: most government teachers reported formal training, while few private-school teachers did so; however, textbook-bound practice persisted across both sectors. Qualitative accounts suggested private-school classrooms were somewhat more student-centred under stronger administrative and parental accountability, whereas government schools were more conventional. Conclusions: Findings reveal a pronounced intended–enacted curriculum gap in secondary science. Despite policy aspirations and substantial training (particularly in the government sector), classroom instruction remains dominated by textbook reading, lecture, and minimally child-centred planning, with limited practical work and few co-curricular science activities. Addressing this misalignment will require aligning assessment with inquiry; strengthening school-level accountability and instructional coaching; expanding low-cost practicals, mobile lab kits, and science-club programming; and embedding meaningful ICT use within teacher professional learning. These steps, implemented within the study area contexts, can make learner-centred, inquiry-oriented science both expectable and doable in everyday practice.